(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: In this modern era, Nursing students’ reliance on digital devices for academic and personal usage is increasing, which particularly vulnerable to Computer Vision Syndrome (CVS), a condition attributed to visual discomfort associated with prolonged screen exposure. Nursing students, in particular, may face higher risks due to intensive academic workloads and extended use of electronic health records. Objective: This study aimed to assess the duration of screen time and its association with the prevalence of eye-related problems among nursing students at the College of Nursing, (Female) Badin. Methods: A cross-sectional study was conducted among nursing students at the College of Nursing (Female), Badin. Data collection was done by a structured questionnaire, divided into three sections: 1) Participant demographics were self-directed about age, sex, gender, and year of study. 2) The screen time section had only one question, which was a self-directed and open-ended question about the average screen time of the participant. 3) The CVS-Smart questionnaire was utilized based on its validity and reliability on Computer Vision Syndrome (CVS) criteria. Data was analyzed on 144 samples for Descriptive statistics, Pearson’s correlation, and linear regression were used to evaluate the relationship between screen time and eye symptoms. Results: The majority of participants, 53.95% reported screen use of more than 5 hours per day. Out of 144 participants, 12 participants were considered as Normal subjects, 33 participants were considered as Not-CVS cases, 43 participants were considered as Low-probability cases, 34 participants were considered as high-probability cases, and 22 participants were considered as Positive CVS cases based on CVS- Smart questionnaire scoring. A significant positive correlation was observed between screen time and severity of eye problems (r =0.785, p < 0.05). Linear regression analysis indicated that each additional hour of screen time increased CVS severity scores by 0.782 (p < 0.01). Conclusion: There was a statistically significant association between prolonged screen time and eye problems among nursing students at the College of Nursing, (Female) Badin. These findings highlighted the need for preventive education, ergonomic awareness, and institutional policies to reduce screen-related eye strain in academic environments.